Using focus groups with dairy cattle veterinarians to explore learning about calf welfare. (27th January 2023) - Sumner, Christine L; Bolduc, Naseeb; von Keyserlingk, Marina AG
Abstract: Dairy calf welfare is a growing interest within the veterinary field. However, a limited understanding of the conception of calf welfare by dairy cattle veterinarians can hinder efforts to promote welfare improvements on farms. The aim of this study was to explore how focus groups can promote learning about dairy calf welfare issues among cattle veterinarians. Focus groups (n = 5), that collectively had 33 participants representing five Canadian provinces and different geographical regions, were conducted as part of a continuing education workshop for Canadian cattle veterinarians. Two trained individuals undertook exploratory data analyses using applied thematic analysis and adult learning theory to develop a codebook of the data and identify the main themes. There were three main themes about learning that emerged from guided peer-discussion: (i) defining a shared concept of animal welfare from the veterinary perspective to diagnose the problem; (ii) understanding the problems of calf welfare by self-examination and group reflection; and (iii) negotiating the best approach to address the problems through sharing of ideas on improving calf welfare, including strategies for addressing welfare problems. In conclusion, focus groups can facilitate animal welfare learning within the veterinary profession.